PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN GRAB BIKE DI UNIVERSITAS KRISNADWIPAYANA - David Adista; Donny Dharmawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to analyze the effect of service quality and customer value on GrabBike customer satisfaction at Unkris, Jakarta. This study took a sample of 71 customers from a total of 250 GrabBike customers at Unkris, Jakarta. Samples were taken using the Slovin formula by random sampling method. Data testing techniques used in this study include validity test, reliability test, multiple linear regression analysis to test and prove the research hypothesis. The results of this analysis indicate that the variables of service quality and customer value have a positive and significant influence on customer satisfaction.